Topical Gynura procumbens as a Novel Therapeutic Improves Wound Healing in Diabetic Mice - Nutda Sutthammikorn; Volaluck Supajatura; Hainan Yue; Miho Takahashi; Sunee Chansakaow; Nobuhiro Nakano; Pu Song; Takasuke Ogawa; Shigaku Ikeda; Ko Okumura; Hideoki Ogawa; François Niyonsaba (Plants, 2021)
Nonhealing wounds are major socioeconomic challenges to healthcare systems worldwide. Therefore, there is a substantially unmet need to develop new drugs for wound healing. Gynura procumbens, a herb found in Southeast Asia, may be an effective therapeutic for nonhealing diabetic wounds. The aim of this study was to evaluate the efficacy of G. procumbens on wound healing in the diabetic milieu. G. procumbens extract was obtained using 95% ethanol and its components were determined by thin layer chromatography. Diabetes was induced in mice using streptozotocin. We found that G. procumbens extract contained stigmasterol, kaempferol and quercetin compounds. Topical application of G. procumbens on the wounded skin of diabetic mice accelerated wound healing and induced the expression of angiogenin, epidermal growth factor, fibroblast growth factor, transforming growth factor and vascular endothelial growth factor. Furthermore, G. procumbens promoted in vitro wound healing and enhanced the migration and/or proliferation of human endothelial cells, fibroblasts, keratinocytes and mast cells cultured in diabetic conditions. Finally, G. procumbens promoted vascular formation in the diabetic mice. To the best of our knowledge, this is the first study that evaluates in vivo wound healing activities of G. procumbens and activation of cells involved in wound healing process in diabetic conditions. The findings that G. procumbens accelerates wound healing and activates cells involved in the wound healing process suggest that G. procumbens might be an effective alternative therapeutic option for nonhealing diabetic wounds.